Potencial crioprotetor da β-glucana de levedura descartada em cervejarias em culturas de Lactobacillus probióticos - Guedes, Jéssica da Silva (2019)
Freeze-drying is a widely used method to protect probiotic cultures applied in the food industry. However, that process damages the cells by decreasing their viability during storage and may compromise their physiological functionality of exerting benefits to the host. The use of carbohydrates has been used as a strategy to protect probiotic cells during freeze-drying. The β-glucan is a homopolymer of glucose well-known for bioactive properties which can be obtained from discarded yeast in biotechnological processes. The aim of this study was to evaluate the potential of β-glucan extracted from spent brewer yeast (YβG) as a protective agent of three probiotic cultures of Lactobacillus (L. acidophilus LA-05, L. plantarum 49, and L. plantarum 201) during freeze-drying, refrigerated storage and exposure to simulated conditions of the gastrointestinal tract (SGIT). The integrity of the membrane and the ultrastructure of freeze-dried cells with and without YβG were also evaluated. Fructo-oligosaccharide (FOS), a recognized as cryoprotectant, was used for comparison purposes and saline solution was used as control. YβG showed protective effect and similar effect to that obtained with FOS during freeze-drying, storage of 90 days and exposure to SGIT conditions in all probiotic strains tested. The effect of YβG during storage and SGIT varied among the strains tested, with the best results observed in the assays with L. plantarum 201. Freeze-dried samples with saline solution showed a reduction of up to 4 log CFU / g, as well as the highest percentage of cells with damaged membrane. Micrographs of freeze-dried cells of L. plantarum 201 showed the strain adhered to β-glucan and produced exopolysaccharide. The results show that β-glucan extracted from discarded yeast in breweries can be used as a cryoprotectant of lactobacilli strains during freeze-drying, refrigerated storage of up to 90 days and when exposed to simulated SGIT conditions presenting potential application as a functional food ingredient.